Weathered tropical soils: the ultisols & oxisols - Jusop, Shamshuddin; Ishak, Che Fauziah (Universiti Putra Malaysia Press, 2010)
This book is published primarily to summarize the research carried out on two of the most important soils in Malaysia. These two types of soils which cover about 70% of our land surface are mainly used for cultivation of oil palm and rubber, the backbone of our economy. The main beneficiaries of the book are students of soil mineralogy, chemistry annd fertility as well as those studying in public universities in Malaysia. Others are soil scientists and agronomists who work in the public and private sectors. This book is written in 10 chapters, covering the various aspects of soil science. These include soil formation and classification, the soils physico-chemical properties and how Ultisols and Oxisols in Malaysia are managed for sustainable crop production.